2013
DOI: 10.1016/j.compeleceng.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

A privacy-aware access control model for distributed network monitoring

Abstract: Despite the usefulness of network monitoring for the operation, maintenance, control and protection of communication networks, as well as law enforcement, network monitoring activities are surrounded by serious privacy implications. Their inherent leakage-proneness is harshened due to the increasing complexity of the monitoring procedures and infrastructures, that may include multiple traffic observation points, distributed mitigation mechanisms and even inter-operator cooperation. However, current approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 55 publications
0
4
0
2
Order By: Relevance
“…With the mechanisms outlined above, the proposed framework lays the foundation for the incorporation, during workflow design, of sophisticated security policies enforceable at runtime. Going a step further, it interworks with a state‐of‐the‐art privacy‐aware access control model [45], also developed within DEMONS, supporting the automatic verification of workflows compliance with privacy principles and their enhancement with related features already at design‐time [46]. Therefore its suitability for the particular application domain has also been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…With the mechanisms outlined above, the proposed framework lays the foundation for the incorporation, during workflow design, of sophisticated security policies enforceable at runtime. Going a step further, it interworks with a state‐of‐the‐art privacy‐aware access control model [45], also developed within DEMONS, supporting the automatic verification of workflows compliance with privacy principles and their enhancement with related features already at design‐time [46]. Therefore its suitability for the particular application domain has also been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that even non-intrusive smart-meters enable the accurate tracking of a person's location within the house, e.g., by detecting changes in lighting or other frequently used devices, or enable the estimation of working routines and the number of people living in a household [31,32]. As these data are very personal and could even be related to security issues, e.g., working routines could be observed and used by criminals to plan burglaries, studies on the encryption of energy data have been presented in [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, significant progress in smart grids, smart systems, and smart devices was made in the last few decades, considering optimized energy generation and distribution [9,10]. Accordingly, energy management and the deployment of Information and Communication Technologies (ICT) in residential buildings increased as well, in order to reduce households' energy consumption without decreasing living quality levels or violating consumers personality rights and privacy [11,12]. In general, the amount of information gathered is increased progressively with respect to consumer behavior.…”
Section: Introductionmentioning
confidence: 99%